2012
DOI: 10.1259/bjr/30974918
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the underestimation rate in cases with ductal carcinoma in situ at ultrasound-guided core biopsy: 14-gauge automated core-needle biopsy vs 8- or 11-gauge vacuum-assisted biopsy

Abstract: Objective: The objective of this study was to compare the underestimation rate of invasive carcinoma in cases with ductal carcinoma in situ (DCIS) at percutaneous ultrasound-guided core biopsies of breast lesions between 14-gauge automated coreneedle biopsy (ACNB) and 8-or 11-gauge vacuum-assisted biopsy (VAB), and to determine the relationship between the lesion type (mass or microcalcification on radiological findings) and the DCIS underestimation rate. Methods: We retrospectively reviewed imaging-guided bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
21
1
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(30 citation statements)
references
References 38 publications
6
21
1
2
Order By: Relevance
“…This result is identical to the rates reported by previous studies that used VAB (8-G or 10-G) devices and found that the DCIS underestimation rates decreased with larger acquired tissue samples, which were attributed to decreases in sampling errors [11, 16]. Furthermore, our underestimation rate with CCNB (28.2%) was lower than that of reported by previous studies (39%–67%) [11, 1821]. Our routine CCNB practice involves the collection and review of >4 non-fragmented samples by a single, dedicated breast pathologist, which may explain our lower underestimation rate.…”
Section: Discussionsupporting
confidence: 90%
“…This result is identical to the rates reported by previous studies that used VAB (8-G or 10-G) devices and found that the DCIS underestimation rates decreased with larger acquired tissue samples, which were attributed to decreases in sampling errors [11, 16]. Furthermore, our underestimation rate with CCNB (28.2%) was lower than that of reported by previous studies (39%–67%) [11, 1821]. Our routine CCNB practice involves the collection and review of >4 non-fragmented samples by a single, dedicated breast pathologist, which may explain our lower underestimation rate.…”
Section: Discussionsupporting
confidence: 90%
“…DCIS underestimation rates in patients diagnosed by CNB were about 10–40% 8, 10, 15, 16, which compared to the 5% of surgical excision and 13% of 11‐guaze VAB biopsy found in previous studies 16, 17. DCIS underestimation tends to decline as the retrieved volume of the specimen increases, which suggests that the retrieved volume of the specimen and the type of biopsy methods are important factors affecting the DCIS underestimation rate 18. In general, 8 or 11‐guage VAB is considered a more accurate tool in confirming benign or malignant lesions than 14‐guage CNB.…”
Section: Discussionmentioning
confidence: 73%
“…One study has demonstrated that 95 % non-mass-like breast lesions on US also appeared as non-mass enhancement on magnetic resonance imaging (MRI), and it was also difficult for MRI to provide a differential diagnosis for these non-mass breast lesions [7]. Also, it has been reported that the histological agreement rate between US-guided core-needle biopsy and surgical histological diagnosis was significantly better for mass lesions than for non-mass-like lesions on US [8][9][10]. Therefore, an in-depth study of the US features of non-mass-like breast carcinoma appears to be of major importance.…”
Section: Discussionmentioning
confidence: 99%